2004
DOI: 10.1002/jsfa.1676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preharvest applied herbicides on breadmaking quality of hard red spring wheat

Abstract: Certain herbicides can be applied prior to harvest for weed control in wheat. Research was conducted to determine the effect of preharvest applications of glyphosate, paraquat and metsulfuron + 2,4-D on grain, flour and the breadmaking quality of hard red spring wheat. Herbicides were applied at soft dough (SD), ∼500 g kg −1 kernel moisture and hard dough (HD), ∼350 g kg −1 kernel moisture stages of 'Parshall' hard red spring wheat. Test weight was reduced 1.3 and 2.3 kg hl −1 , 1000 kernel weight was reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 18 publications
2
20
1
Order By: Relevance
“…According to the literature, an FN > 300 indicates low α‐amylase activity, whereas values of approximately 200 to 250 are indicative of normal enzyme activity (Caglar and others ; Bulut and others ). Although variations in FN values were found as a consequence of some aspects of crop management such as fertilizer type, weeding management (Bulut and others ) or seeding rates (Caglar and others ), no difference was found in relation to the application of different herbicides (Manthey and others ). A reduction in the FN is common in ripe wheat grain in which preharvest sprouting occurs (Humphreys and Noll ), but according to recent studies (Mares and Mrva ), a significant production of late maturity α‐amylase (LMA) is frequently detected independent of sprouting in commercially grown wheat.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, an FN > 300 indicates low α‐amylase activity, whereas values of approximately 200 to 250 are indicative of normal enzyme activity (Caglar and others ; Bulut and others ). Although variations in FN values were found as a consequence of some aspects of crop management such as fertilizer type, weeding management (Bulut and others ) or seeding rates (Caglar and others ), no difference was found in relation to the application of different herbicides (Manthey and others ). A reduction in the FN is common in ripe wheat grain in which preharvest sprouting occurs (Humphreys and Noll ), but according to recent studies (Mares and Mrva ), a significant production of late maturity α‐amylase (LMA) is frequently detected independent of sprouting in commercially grown wheat.…”
Section: Resultsmentioning
confidence: 99%
“…Despite some differences seen depending on the wheat sample, the presence of 6–11 mg kg −1 of glyphosate in whole‐grain flour had minor effects on dough and bread properties, confirming results obtained by others with lower levels of glyphosate in bran‐free flours (Darwent et al ., ; Manthey et al ., ). Not reported previously, glyphosate application in the field did not change the level of fructans in wheat kernels.…”
Section: Discussionmentioning
confidence: 97%
“…Glyphosate residues in mature wheat would have little effects on the bread-making potential of white flour, including dough mixing tolerance and bread volume Manthey et al, 2004;Craven et al, 2007). However, whole-grain flour would be more contaminated than white flour because pesticides residues accumulate on the external portions of wheat kernels (Amvrazi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Literature is limited on the impact of preharvest glyphosate applied with AMS at different timings. Manthey et al (7) found that glyphosate applied alone at the hard dough stage at the rate of 0.75 lb acid equivalent/acre did not affect grain protein content but did increase gluten index two to eight units in HRSW. Preharvest glyphosate applied alone to HRSW with grain moisture below 25% did not alter grain protein content but did increase grain yield in some locations compared with the windrowed control (5).…”
Section: Findings Of the Field Experimentsmentioning
confidence: 99%
“…Glyphosate − a broad-spectrum systemic herbicide used to control annual and perennial species of both grassy and broadleaf weeds − is registered as a harvest aid in wheat (6,7). Preharvest applications of glyphosate have been shown to effectively facilitate wheat dry-down through chemical desiccation and is considered more dependable and economical than the traditional method of windrowing (4,5,7).…”
Section: Introductionmentioning
confidence: 99%